NON-CONVENTIONAL AGRICULTURAL LAND USE: A WAY TO ACCELERATE ECOLOGIZATION AND CAPITALIZATION - Anton TRETIAK; Valentina TRETIAK; Tatyana PRIADKA; Valeriy LYASHYNSKYY; Nataliia TRETIAK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article is devoted to the prospect of introducing innovative measures in agriculture, which will contribute to the growth of agricultural production in Ukraine. In particular, the authors researched the development of non-conventional land use as a path to greening and capitalizing land use of peasant farms and individual farms, as well as small and medium-sized enterprises in the context of growing organic and niche products. In the course of the analysis, the article examines the state of the use of the land fund in Ukraine, namely, by grouping of the average size land plots of agricultural shares owners. Which made it possible to divide the regions into six groups and show that with an increase in the area of agricultural land in the regions, the intensity of its use also increases, this contributes to degradation processes and, in general, less efficient use of land. As an example, the share of sunflower in the total crop structure is presented, and it exceeds the standards by almost 2 times. The authors of the article noted the fact that the forms and sizes of land use of agricultural enterprises are of great importance for the efficiency of land use. In particular, the structure of operating agricultural enterprises in Ukraine by the size of agricultural land is presented, which made it possible to note a significant percentage of small farms (56.7%). This allows us to conclude that the current trends require a reorientation of the development of land use by individual farms, peasant farms, as well as small and medium-sized enterprises to non-conventional, which foresees the use of innovative measures for the production of organic and niche crops, this will allow them to exist in the agricultural market. From an environmental and economic point of view, the cultivation of organic and niche products will contribute to an increase in labor productivity in rural areas, an increase in the production at individual farms, peasant farms, as well as at small and medium-sized enterprises, and in general, will accelerate the greening and capitalization of land use. As the land use is both a place of work and a territory of residence for land share owners and farmers. The authors present agricultural crops that are in demand both for export and for consumption inside the country.